ER, p53 and MIB-1 are significantly associated with malignant phyllodes tumor - Nurhayati H Munawer (Biomedical Journal, 2012)
Background: Phyllodes tumors (PT) are rare. We evaluated the expression status of ER, Bcl2, p53, and MIB-1 protein in these tumors. Methods: One hundred and ninety-three tumors were examined using immunohistochemistry on tissue microarray. Results: ERβ (p <0.001), and p53 (p=0.006) in the stromal component were associated with tumor size. p53 expression was significantly associated with both epithelial and stromal components of malignant PTs (p<0.05). In PT, the decreased expressions of p53 and MIB-1 were significantly different with positive Bcl2 protein expression in epithelial component (p=0.000). Besides, MIB-1 was also found to be associated with ERα and ERβ in stromal component (p=0.000). Conclusion: The expression of p53 with tumor size and histological grade in PTs may increase risk for malignancy.